2019
DOI: 10.5812/ircmj.87754
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Assessment of Anti-Leishmanial Efficacy of Leaf, Fruit, and Fractions of Juniperus excelsa Against Axenic Amastigotes of Leishmania major and Topical Formulation in BALB/c Mice

Abstract: Background: Leishmaniasis is a parasitic disease caused by Leishmania protozoa. Iran is an endemic region for leishmaniasis and thus, many natural medicaments, such as Juniperus excelsa, are traditionally being used for the treatment of its cutaneous form. Objectives: The current study aimed at assessing the anti-leishmanial activities of this medicament's leaf and fruit extracts and respective leaf fractions against Leishmania major as the causative agent of zoonotic cutaneous leishmaniasis in both in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…For example, in an in vivo study, the anti‐leishmaniasis effect of barberry was proven 24 . Furthermore, the anti‐leishmanial activity of the extract of fruits and leaves of Juniperus excelsa M. Bieb has been proven in both in vitro and in vivo studies 25 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in an in vivo study, the anti‐leishmaniasis effect of barberry was proven 24 . Furthermore, the anti‐leishmanial activity of the extract of fruits and leaves of Juniperus excelsa M. Bieb has been proven in both in vitro and in vivo studies 25 26 .…”
Section: Resultsmentioning
confidence: 99%
“…24 Furthermore, the anti-leishmanial activity of the extract of fruits and leaves of Juniperus excelsa M. Bieb has been proven in both in vitro and in vivo studies. 25 In another in vitro study, the antileishmaniasis effect of the extract of leaf of Aloe vera was revealed. 26 In addition, one clinical trial has shown that the extract of Nigella sativa L. mixed with honey accelerates the healing process of CL lesions.…”
Section: Manipulationmentioning
confidence: 98%
“…The concentration of methanolic extract for antileishmanial assay in the cream formulation was considered to be 10% (W/W). The placebo cream was also prepared in the same manner (Mirzavand et al, 2019).…”
Section: Extraction Fractionation and General Proceduresmentioning
confidence: 99%